Clinical outcomes of imatinib dose escalation versus sunitinib in first-line imatinib-failure gastrointestinal stromal tumour. (2nd November 2018) - Yang, Weili; Li, Kai; Yu, Jiren; Shou, Chunhui; Zhang, Qing; Hong, Yanyun; Sun, Jianyi; Yu, Hang; Gao, Yuan; Shen, Qianyun; Zhao, Zhicheng; Zheng, Shusen
Abstract: Aim: The majority of available data on the clinical efficacy of sunitinib in patients with imatinib-resistant or -intolerant gastrointestinal stromal tumours (GISTs) are from studies of western populations. We investigated the clinical outcomes of imatinib dose escalation versus sunitinib in first-line imatinib-failure Asian GIST patients to further guide clinical treatment. Methods: Patients received imatinib dose escalation and a shift to sunitinib (Group A) or a direct shift to sunitinib (Group B). The objective tumour response was assessed according to Choi's criteria. Progression-free survival (PFS) and overall survival (OS) were calculated. The relationship between genetic mutation and survival was analysed. Results: In total, 40 patients who fulfilled the inclusion criteria were recruited. The differences in survival between Group A and Group B were not significant for PFS ( p  = .776) or OS ( p  = .219). For patients with KIT exon 11 mutation, a trend towards a better PFS was found in Group B ( p  = .122), OS of Group B was better than Group A ( p  = .013). The median PFS and OS of sunitinib treatment were 8 and 24 months, respectively, and a clinical benefit was observed in 80%. Patients with KIT exon 11 mutations had better PFS compared to those with KIT exon 9 mutations or wild-type GISTs ( p  = .017, p  = .040, respectively). Conclusions: Both imatinib dose escalation and sunitinib were optional in Asian patients after failure of first-line imatinib, and patients with KIT exon 11 mutation benefited more from a direct shift to sunitinib.